The Controversy of Water Resources Legislation in Indonesia: an Islamic Constitutional Law Approach - Suntana, Ija (Jurnal Hukum Islam, 2021)
This study aims to explain the protracted water legislation controversy in Indonesia. Any birth law on water resources always raises the pros and cons of the Indonesian people. This study is descriptive-analytical research, with a socio-political, juridical normative, and doctrinal approach. This study finds that the cause of the controversy over water legislation in Indonesia is that references of legislation do not stand on a solid concept, as conceptualized in the Islamic constitutional law, namely meaning of the legal text, social realities, proportional between maslahat and mafsadat, the priority of content rules and law changes.